Electoral realignments : a critique of an American genre - Mayhew, David R. (Yale ISPS series., 2002)
"The study of electoral realignments is one of the most influential and intellectually stimulating enterprises undertaken by American political scientists. Realignment theory has been seen as a science able to predict changes, and generations of students, journalists, pundits, and political scientists have been trained to be on the lookout for "signs" of new electoral realignments. Now a major political scientist argues that the essential claims of realignment theory are wrong - that American elections, parties, and policy making are not (and never were) reconfigured according to the realignment calendar. David R. Mayhew is Sterling Professor of Political Science at Yale University."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved